Neonatal Pharmacokinetics and Biodistribution of Polymeric Nanoparticles and Effect of Surfactant - Nuo Xu; Megan Wong; Gabrielle Balistreri; Elizabeth Nance (MDPI AG, 2023)
The development of therapeutics for pediatric use has advanced in the last few decades, yet the off-label use of adult medications in pediatrics remains a significant clinical problem. Nano-based medicines are important drug delivery systems that can improve the bioavailability of a range of therapeutics. However, the use of nano-based medicines for application in pediatric populations is challenged by the lack of pharmacokinetic (PK) data in this population. To address this data gap, we investigated the PK of polymer-based nanoparticles in term-equivalent neonatal rats. We used poly(lactic-co-glycolic acid)-poly(ethylene glycol) (PLGA-PEG) nanoparticles, which are polymer nanoparticles that have been extensively studied in adult populations but less commonly applied in neonates and pediatrics. We quantified the PK parameters and biodistribution of PLGA-PEG nanoparticles in term-equivalent healthy rats and revealed the PK and biodistribution of polymeric nanoparticles in neonatal rats. We further explored the effects of surfactant used to stabilize PLGA-PEG particles on PK and biodistribution. We showed that 4 h post intraperitoneal injection, nanoparticles had the highest accumulation in serum, at 54.0% of the injected dose for particles with Pluronic® F127 (F127) as the stabilizer and at 54.6% of the injected dose for particles with Poloxamer 188 (P80) as the stabilizer. The half-life of the F127-formulated PLGA-PEG particles was 5.9 h, which was significantly longer than the 1.7 h half-life of P80-formulated PLGA-PEG particles. Among all organs, the liver had the highest nanoparticle accumulation. At 24 h after administration, the accumulation of F127-formulated PLGA-PEG particles was at 26.2% of the injected dose, and the accumulation of P80-formulated particles was at 24.1% of the injected dose. Less than 1% of the injected nanoparticles was observed in healthy rat brain for both F127- and P80-formulated particles. These PK data inform the use of polymer nanoparticle applications in the neonate and provide a foundation for the translation of polymer nanoparticles for drug delivery in pediatric populations.